Phylogeography and population genetics of two forest endemic mosses in the Cape Floristic Region - McGrath, Kate (Department of Biological Sciences, 2017)
Different histories for forests in Southern Africa have been hypothesized from vegetation biogeography and pollen analysis. However, the history of forests is still controversial. Phylogeography uses gene genealogies to infer history of distributions. Two forest endemic moss species were sampled: Leptodon smithii; and Neckera valentiniana. Two gene regions were used, trnLF (chloroplast genome) and ITS1 (nuclear genome). Neckera valentiniana showed no variation from the populations sampled. Results from Leptodon smithii based on the trn and ITS region suggest that forests once were widespread, but then became fragmented. Dispersal corridors still exist between Southern Cape populations and Western Cape populations.